Subjective well-being: Mental health study among student in the Islamic boarding school - Lharasati Dewi; Fatwa Tentama; Ahmad Muhammad Diponegoro (Intelektual Pustaka Media Utama, 2021)
The purpose of this study was to analyze the model of the influence of family social support, gratitude, and self-acceptance on subjective well-being in student in Islamic boarding schools. The population in this study was all student of class VII in boarding school X and boarding school Y in Yogyakarta, with a total of 430 students. The sample in this study was 150 students. The sampling technique used for this study was cluster random sampling. The data were collected by using several instruments in the form of scales. The scales consisted of family social support scale, gratitude scale, self-acceptance scale, and subjective well-being scale. Data analysis was performed by testing the outer model and the inner model. The data were analyzed using structural equation model (SEM) through the Smart Partial Least Square 3.2.8 program. The results of this study suggested that the formation of a model of the influence of family social support, gratitude, and self-acceptance on subjective well-being fits with empirical data obtained. In other words, there was a significant positive correlation between all variables being studied and subjective well-being. The theoretical model formed in this study was considered fit, so it can be used as a valid model reference in investigating adolescents' subjective well-being.